2000
DOI: 10.2113/gscanmin.38.4.861
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahedrally Coordinated Boron in a Tourmaline: Boron-Rich Olenite From Stoffhutte, Koralpe, Austria

Abstract: The substitution of [4] B for [4] Si in tourmaline has been the source of much discussion. A sample of olenite from Stoffhütte, Koralpe, Styria, Austria has been found to contain more than one [4] B per formula unit of 31 (O,OH,F), demonstrating that significant [4] B = [4] Si substitution does indeed occur in tourmaline. The composition of the structurally characterized crystal was determined using electron microprobe and SIMS data; in combination with refinement of the site scattering, the chemical data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 11 publications
1
31
0
Order By: Relevance
“…Schreyer et al (2000) and Marler and Ertl (2002) reported low-field 11 B MAS NMR spectra of a synthetic olenite with a nominal T-site content of Si 3 B 3 , and a [4] B-bearing olenite from a granitic pegmatite. Ertl et al (1997) and Hughes et al (2000Hughes et al ( , 2001 have shown that <T-O> distances in the tourmaline examined by Marler and Ertl (2002) are in accord with the presence of [4] B, and similar stereochemical results have been reported (Hughes et al 2004;Kalt et al 2001;Ertl et al 2005Ertl et al , 2006Ertl et al , 2007 indicating the presence of [4] B in Li-bearing tourmaline.…”
Section: Previous Worksupporting
confidence: 59%
See 1 more Smart Citation
“…Schreyer et al (2000) and Marler and Ertl (2002) reported low-field 11 B MAS NMR spectra of a synthetic olenite with a nominal T-site content of Si 3 B 3 , and a [4] B-bearing olenite from a granitic pegmatite. Ertl et al (1997) and Hughes et al (2000Hughes et al ( , 2001 have shown that <T-O> distances in the tourmaline examined by Marler and Ertl (2002) are in accord with the presence of [4] B, and similar stereochemical results have been reported (Hughes et al 2004;Kalt et al 2001;Ertl et al 2005Ertl et al , 2006Ertl et al , 2007 indicating the presence of [4] B in Li-bearing tourmaline.…”
Section: Previous Worksupporting
confidence: 59%
“…Single-crystal structure refinements suggest that the <T-O> distance in tourmaline is sensitive to the presence of [4] B (Hughes et al 2000(Hughes et al , 2004Ertl et al 1997Ertl et al , 2005Ertl et al , 2006Ertl et al , 2007. However, this type of relation is not yet at the stage of being a predictive compositional tool, partly because of the possibility that Al may also occur at the T site and perturb any possible relation between <T-O> and [4] B content.…”
Section: Previous Workmentioning
confidence: 99%
“…This tourmaline from Eibenstein has the highest known Al content of all natural tourmalines (up to 47.08 wt% Al 2 O 3 ; up to ∼8.64 apfu Al). Very high Al contents were also found in colorless (B-rich) olenite from Koralpe, Styria, Austria (up to 46.53-46.71 wt% Al 2 O 3 and 8.46 apfu Al; Ertl et al 1997;Hughes et al 2000), and in olenite from the type locality, Olenii Range, Voron i Tundry, Kola Peninsula, Russia (up to 45.79-46.43 wt% Al 2 O 3 and 8.52 apfu Al; Sokolov et al 1986;Schreyer et al 2002). Structural refi nements of the X site of both samples confi rm Na occupancy of <50% [ Table 2; only very small amounts of Ca (0.04 wt% CaO) and K (0.01 wt% K 2 O) were found by chemical analyses (Table 4)].…”
Section: Structurementioning
confidence: 97%
“…There has been considerable work done on the characterization (e.g. Hawthorne et al, 1993;Burns et al, 1994;Taylor et al, 1995;Dyar et al, 1998;Francis et al, 1999;Bloodaxe et al, 1999;Kalt et al, 2001;Cámara et al, 2002;Schreyer et al, 2002;Ertl and Hughes, 2002;Ertl et al, 2003aErtl et al, ,b, 2004Ertl et al, , 2005Hughes et al, 2000Marschall et al, 2004;Bosi et al, , 2005 and understanding (Hawthorne, 1996(Hawthorne, , 2002 of site occupancy in tourmaline. However, the complete derivation of site populations (and accurate bulk compositions) is not trivial, and our knowledge of the crystal chemistry of all the tourmaline minerals is still far from complete.…”
Section: Introductionmentioning
confidence: 99%